PENDIDIKAN KARAKTER MORAL PRAMUKA PADA KETERAMPILAN BERBICARA SISWA SMK SWASTA SURABAYA - Navira Surya Andani; Resdianto Permata Raharjo; Titik Indarti (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
The urgency of students' speaking skills needs to be improved through moral character education in scouts. The purpose of this study is to determine the importance of the correlation of moral education that can improve speaking skills. This study uses a qualitative approach with interview and observation data collection methods. From this study, it can be seen that students' problems when speaking include 1) pronunciation accuracy, 2) use of diction, 3) attitude gestures, 4) ability to choose topics, 5) coherence, 6) voice and intonation, and 7) fluency. The benefits of scouts found include strengthening character formation, growing strong mental and morals, having an attitude of tolerance needed as a means of developing self-potential. The conclusions obtained in the form of various problems of speaking skills can be overcome by inculcating moral education, support from the school and family is also needed in student activities to participate in scouting to instill moral values that become the basis for improving students' speaking skills. Keywords: Speaking Skills, Moral Education, Scouts